Analisis Dinamik Model Predator-Prey dengan Efek Pemanenan Pada Populasi Ikan Nike (Awaous Melanocephalus) di Provinsi Gorontalo - Usman, Nunung; Nento, Abdul Djabar; Hendri, Excel Muhammad; Biga, Azril Saputra; Sigar, Leidi; Nuha, Agusyarif Rezka (Jurusan Matematika FMIPA UNM, 2024)
Gorontalo Province is one of the areas directly adjacent to Tomini Bay, which is known for its rich natural resources, especially in the fisheries sector such as Nike fish (Awaous melanocephalus). Nike fish is the main food commodity for people in the Gorontalo region. However, intensive fishing activities can pose an extinction threat to this species. This study aims to understand the dynamics of the Nike fish population using a predator-prey model that integrates the effects of harvesting on the prey population. The research process includes formulation of assumptions, model building, model validation, and data analysis through mathematical analysis and numerical simulation. The analysis showed that the model has four equilibrium points, each with different stability conditions. Numerical simulations showed that an increase in harvesting rate and natural mortality of prey, as well as a decrease in birth rate, could threaten the viability of the Nike fish population. Thus, appropriate management efforts are needed to maintain ecosystem balance and the sustainability of the Nike fish population. The calculation results show that the Nike fish production threshold in Gorontalo Province is 8.470.858 kg per year. However, the amount of Nike fish production in Gorontalo Province in 2023 only reached 56,75% of the threshold. This indicates that the production of Nike fish in Gorontalo can still be increased as long as the harvest limit is observed to prevent extinction.